Induction-assisted direct laser deposition of Inconel 625 on DS Rene125: Microstructure, texture, and porosity control - Fareed Kermani; Hossein Momeni; Reza ShojaRazavi; MohammadReza Borhani (Journal of Materials Research and Technology)
This study pioneers directional substrate-engineered direct laser deposition (DLD) on DS-Rene 125 turbine blade, leveraging induction heating to extreme axial thermal gradients and suppress off-axis dendrite nucleation. Advanced characterization methods, including optical microscopy, SEM, and XRD(equipped with a goniometer), were employed to analyze the microstructural evolution. Microstructural observations revealed that the application of the induction coil significantly altered dendrite orientation, increasing the angle from 67° to 86° relative to the horizontal axis. Furthermore, the induction coil induced a Columnar-to-Equiaxed Transition (CET) delay, accompanied by a 32 % expansion of the columnar grain region. Induction coil enhances vertical thermal gradients, modifies melt pool dynamics, and induces vortex flows, enabling 100 % gas porosity elimination in DLD. Pole figure analysis demonstrated a 100 % enhancement in maximum texture intensity along the <100> crystallographic direction, while the <110> texture intensity diminished by 60 %. This indicates improved heat transfer along the z-axis and reduced lateral thermal dissipation, leading to a more prominent <100> texture and reduced equiaxed structure formation.